Low-cost in-house re-formulated brain heart infusion medium for effective planktonic growth and early detection of bloodstream bacterial pathogens - Hira, Jonathan; Mahbub, Nasib Bin; Ali, Jawad; Ahmad, Rafi (Frontiers in Microbiology, 2025)
Sepsis, a clinically defined life-threatening condition, is a global contributor to high morbidity and mortality rates in humans. It is caused by systemic bloodstream bacterial infections, primarily involving aerobic pathogens such as Escherichia coli, Staphylococcus aureus, and Klebsiella pneumoniae. Rapid and accurate identification of these pathogens is a high-demand task, as prolonged diagnosis may increase the mortality rate among sepsis patients. Globally, commercial blood culture systems like the BD BACTEC™ FX blood culture system, which utilizes BD BACTEC™ PLUS Aerobic/F culture bottles (used in this study), are commonly used to detect aerobic bloodstream infections. However, due to high costs (∼10.00–15.00/bottle), limited availability of culture media (especially in low- and middle-income countries, and war zones), and a lack of customization for antibiotic susceptibility assay and epidemiology research, there is a need for secondary alternatives to facilitate the growth and identification of bloodborne pathogens. Therefore, we developed a low-cost (∼4–5/bottle) in-house culture medium with a newly improved formulation of Brain Heart Infusion media that enhances bacterial growth from spiked human blood tested on a panel of bacteria (Escherichia coli, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterococcus faecalis). The growth dynamics of these microbes in in-house formulated BHI-Blood+ culture media coincide with those in BACTEC™ Plus Aerobic/F culture vials, which primarily suggests the compatibility of bloodborne pathogens with this media and can be flagged positive <8 h based on cellular growth rate. Additionally, conventional qPCR-based early detection (<24 h) and validation with the Oxford Nanopore MinION NGS platform highlight the value of this in-house culture media as an alternative to commercial culture media in terms of low-cost availability.